1991
DOI: 10.1002/chin.199108195
|View full text |Cite
|
Sign up to set email alerts
|

ChemInform Abstract: One‐Pot Synthesis of Polyfunctionally Substituted 2,3‐Dihydrothiazoles and Thiazolidinones.

Abstract: ChemInform is a weekly Abstracting Service, delivering concise information at a glance that was extracted from about 100 leading journals. To access a ChemInform Abstract of an article which was published elsewhere, please select a “Full Text” option. The original article is trackable via the “References” option.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 1 publication
0
2
0
Order By: Relevance
“…The reaction of non-ionizable compounds with bromoacetyl bromide affords the thiazolidin-5-ones by KBr and HBr elimination ( Fig. 8) [22,23].…”
Section: -Thiazolidinonesmentioning
confidence: 99%
See 1 more Smart Citation
“…The reaction of non-ionizable compounds with bromoacetyl bromide affords the thiazolidin-5-ones by KBr and HBr elimination ( Fig. 8) [22,23].…”
Section: -Thiazolidinonesmentioning
confidence: 99%
“…4-Thiazolidinones have been shown to act as antidiabetic agents via the inhibition of PPARγ enzyme. A recent molecular modeling study on 2-thioxo-4thiazolidinone derivatives (22) using the crystal structure of PPARγ (PDB ID: 2PRG) revealed that the 2thioxothiazolidin-4-one scaffold fits well in the active site and also shows a good overlap with the thiazolidiendione (TZD) group of rosiglitazone, which is a bound inhibitor in the crystal structure and a clinically approved antidiabetic drug. The presence of an unsaturated linker in the derivatives is positive for the PPARγ binding activity, while substitutions of hydrophobic groups with the phenyl ring show a negative impact [97].…”
Section: -Thiazolidinones As Type III Secretion System Inhibitormentioning
confidence: 99%